A Pilot Study of Multidimensional Diffusion MRI for Assessment of Tissue Heterogeneity in Prostate Cancer. Issue 12 (December 2021) - Langbein, Björn J.; Szczepankiewicz, Filip; Westin, Carl-Fredrik; Bay, Camden; Maier, Stephan E.; Kibel, Adam S.; Tempany, Clare M.; Fennessy, Fiona M.
Abstract : Objectives: The objectives of this exploratory study were to investigate the feasibility of multidimensional diffusion magnetic resonance imaging (MddMRI) in assessing diffusion heterogeneity at both a macroscopic and microscopic level in prostate cancer (PCa). Materials and Methods: Informed consent was obtained from 46 subjects who underwent 3.0-T prostate multiparametric MRI, complemented with a prototype spin echo–based MddMRI sequence in this institutional review board–approved study. Prostate cancer tumors and comparative normal tissue from each patient were contoured on both apparent diffusion coefficient and MddMRI-derived mean diffusivity (MD) maps (from which microscopic diffusion heterogeneity [MKi] and microscopic diffusion anisotropy were derived) using 3D Slicer. The discriminative ability of MddMRI-derived parameters to differentiate PCa from normal tissue was determined using the Friedman test. To determine if tumor diffusion heterogeneity is similar on macroscopic and microscopic scales, the linear association between SD of MD and mean MKi was estimated using robust regression (bisquare weighting). Hypothesis testing was 2 tailed; P values less than 0.05 were considered statistically significant. Results: All MddMRI-derived parameters could distinguish tumor from normal tissue in the fixed-effects analysis ( P < 0.0001). Tumor MKi was higher ( P < 0.05) compared with normal tissue (median, 0.40; interquartile range, 0.29–0.52 vs 0.20–0.18; 0.25), as was tumor microscopic diffusion anisotropy (0.55; 0.36–0.81 vs 0.20–0.15; 0.28). The MKi could not be predicted (no significant association) by SD of MD. There was a significant correlation between tumor volume and SD of MD ( R 2 = 0.50, slope = 0.008 μm 2 /ms per millimeter, P < 0.001) but not between tumor volume and MKi. Conclusions: This explorative study demonstrates that MddMRI provides novel information on MKi and microscopic anisotropy, which differ from measures at the macroscopic level. MddMRI has the potential to characterize tumor tissue heterogeneity at different spatial scales.